Strategic Agility Influencing Human Resource Practices in the UAE Ministry of Interior - Alnuaimi, Saeed Mohammad Ebrahim Alkhayyal; Eni, Sabariah (Tropical Scientific Journal, 2025)
Objective: This study aims to investigate the impact of strategic agility on human resource management (HRM) within the United Arab Emirates (UAE) Ministry of Interior (MoI), with a particular focus on how agile practices enhance HR functions amid bureaucratic and operational challenges Research Method: This study aims to investigate the impact of strategic agility on human resource management (HRM) within the United Arab Emirates (UAE) Ministry of Interior (MoI), with a particular focus on how agile practices enhance HR functions amid bureaucratic and operational challenges Findings: The results show that strategic agility significantly influences HRM practices in the MoI. Agile Organizational Structure (β = 0.621, p < 0.001) and Technology and Data-Driven approaches (β = 0.377, p < 0.001) exhibited strong positive effects. Adaptive Leadership had a moderate but significant impact (β = 0.137, p = 0.048). Conversely, Continuous Innovation and Learning showed a significant negative relationship (β = -0.286, p < 0.001), indicating potential difficulties in integrating innovation within existing frameworks. Dynamic Strategy Formulation was found to have no significant effect (β = 0.011, p = 0.756). Originality: This study addresses a critical gap in empirical research by examining the role of strategic agility in public sector HRM, specifically within the context of the UAE Ministry of Interior. It highlights the dual role of enabling factors such as organizational structure and technology, alongside barriers like innovation resistance, offering actionable insights for HR transformation in public institutions